2012
DOI: 10.5772/56169
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Optical and Electrical Properties of ZnFe2O4 Nanocomposites

Abstract: ZnFe2O4 nanocomposites have been prepared by a simple co-precipitation method. The prepared samples were characterized by Scanning Electron Microscopy (SEM), Powder X-ray Diffraction (XRD), Energy Disperse X-ray Analysis (EDX), Transmission electron microscopy (TEM) and UV-visible absorption spectral techniques. Conductivity measurements show a transition from ferrimagnetism to paramagnetism. The enhancement in fluorescence spectra shows that there is an electronic transition to an exciting level. In UV-Vis sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
(24 reference statements)
0
13
0
1
Order By: Relevance
“…This is confirmed from the negative thermal coefficient (NTC) (α) in graphs 4 (b). It is clearly found that the α value increases with increase in concentration of the TiO 2 in OPANI matrix indicates that the thermal resistance of the matrix enhances due to the strong bonding between TiO 2 nanoparticles and matrix [16] The negative coefficient value shows that these materials act as semiconductor at higher temperature [17]. When the temperature rises up, the average amplitude of the atoms vibration within the matrix increases.…”
Section: Conductivitymentioning
confidence: 98%
“…This is confirmed from the negative thermal coefficient (NTC) (α) in graphs 4 (b). It is clearly found that the α value increases with increase in concentration of the TiO 2 in OPANI matrix indicates that the thermal resistance of the matrix enhances due to the strong bonding between TiO 2 nanoparticles and matrix [16] The negative coefficient value shows that these materials act as semiconductor at higher temperature [17]. When the temperature rises up, the average amplitude of the atoms vibration within the matrix increases.…”
Section: Conductivitymentioning
confidence: 98%
“…Çinko ferrit filmlerinin absorpsiyon spektrumu Şekil 4'te verilmektedir. Optik olarak aktif çinko ferrit filmlerinin Uv-Vis bölgesinde güçlü absorpsiyon yaptığı bilinmektedir (Kumar, 2012). Optik özelliklerin Beer-Lambert yasasıyla örtüştüğünü yaklaşık 334 nm'de tespit edilen güçlü absorpsiyon bandı göstermektedir.…”
Section: Uv-vis Spektrumuunclassified
“…Zinc ferrite (ZnFe2O4) is a spinel oxide that possesses excellent magnetic and electrical properties as well as excellent chemical and thermal stabilities. ZnFe2O4 oxide has received much attention due to its potential applications in detecting gases [4], as an adsorbent material for hot-gas desulfurization [5], in biomedicine [6], for its magnetic, optical and electrical behaviors [7][8][9][10][11] and catalytic application [12,13]. Recently, zinc ferrite has been used as an efficient heterogeneous Fenton catalyst in degrading organic pollutants from an aqueous solution [14][15][16].…”
Section: Introductionmentioning
confidence: 99%